Allegory and Social Pathology in Okky Madasari’s Novel 86 - Nurpramiska, Padinsa; Farkhan, Muhammad; Sayogie, Frans; Doka, Hassan Mohamed (Buletin Al-Turas, 2025)
PurposeThe purpose of this study was to explore social phenomena like social inequality by looking at how they were portrayed in a novel through allegorical elements.  MethodThis research employed a descriptive qualitative method to analyze social phenomena, specifically social inequality, as reflected in the novel 86 by Okky Mandasary. Through content analysis, the study examines words, phrases, and sentences to uncover implicit meanings conveyed through symbolism. Qualitative research is suitable as it explores meanings in verbal forms. Such a descriptive analysis helps identify and interpret societal issues represented in the literary text.  FindingsThe novel reflects societal issues like corruption, sexual deviation, and criminality through allegorical elements. These problems are portrayed as diseases affecting society’s structure. Internal factors like personal desire and opportunity along with external societal influences drive these behaviors. Through content analysis, this study explores how the novel reveals social pathologies as ongoing social phenomena.  ConclusionThis descriptive qualitative content analysis demonstrates that Novel 86 by Okky Madasari functions as a powerful allegory, exposing entrenched social pathologies—corruption, sexual deviation, and criminality—as ongoing societal maladies. The study underscores the value of literary examination in uncovering the complex interplay of individual motivations and broader societal influences that perpetuate these issues.